KINERJA PEMBANGUNAN PEMERINTAH DAERAH KABUPATEN PEKALONGAN - Purwoko Purwoko (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Developmental  process  has been implementasi sing in indonesia  since 1969,  about  almost 45 years. As long as  time developmental mean as  physical developmental in  any aspects meters as GNP, Income Percapita and Economic Growth the indicators coult not described the real developmental results in such country or such area  it is needed  another non eonomic variables as social variables whick some indicators as evendestribusion, evenhealth cares in one composite. Inditional social variabless ould describe development performence of  Pekalongan lokal Government (Kabupaten Pekalongan) more comprehensive. Reminded that developmental performance the main pillar of state stability.